THE INFLUENCE OF COMPANY SIZE, LEVERAGE, PROFITABILITY, PUBLIC SHARE OWNERSHIP, BOARD OF COMMISSIONERS SIZE, AND AUDIT COMMITTEE SIZE ON CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE - Salma Salsabila; Subadriyah Subadriyah (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: This investigation aims to determine the effect of company size, leverage, profitability, public share ownership, board size, and governance audit size on the corporate social responsibility disclosure committee. Methods: This study uses multiple linear regression analysis methods. Results: The findings indicate that a company's size or leverage does not significantly impact CSR disclosure. On the other hand, CSR disclosure was positively and significantly affected by profitability and the size of the board of commissioners. In contrast, profitability and the size of the board of commissioners proved to have a positive and significant effect on CSR disclosure. However, public share ownership and audit committee size did not show a significant impact. The conclusion of this study confirms the importance of profitability and board size in encouraging CSR disclosure, while other factors do not contribute significantly. Keywords : Corporate Social Responsibility, company size, leverage, and profitability.